Retraction Note to "Systematic Investigation of Selected Bio-molecules Potentially Effective in Inhibiting SARS-CoV-2/COVID-19 via In-Silico Analysis" [Fine Chemical Engineering, Volume 5 Issue 2 (2024), 269-294] - Universal Wiser Publisher (Fine Chemical Engineering, 2025)
The Editor-in-Chief and the publisher have retracted the following article: Vanzara, A.; Ambasan, S.; Shrivastav, A.; Patel, S.; Patel, V.; Soni, H.; Trivedi, V. Systematic Investigation of Selected Bio-Molecules Potentially Effective in Inhibiting SARS-CoV-2/COVID-19 via In-Silico Analysis. Fine Chemical Engineering 2024, 5, 269-294. This article has been retracted at the request of the Publisher following a formal complaint by BVG Life Sciences Limited, Pune, India. The complaint highlighted that the data presented in the article originated from work conducted at BVG Life Sciences Limited in 2020 during the employment of one of the authors, Mr. Akash Vanzara. Upon review and confirmation with the authors, it was found that the data was submitted for publication without proper authorization or acknowledgment of BVG Life Sciences Limited, constituting a breach of confidentiality and intellectual property rights. In accordance with COPE’s Retraction Guidelines and to maintain the integrity of the scientific record, this article is retracted. We regret any inconvenience this may have caused to the readers and thank them for their understanding. This decision is made upon our policy on publishing ethics and the COPE guidelines.